Preeklampsia dan Dukungan Suami : Studi Korelasional Di Wilayah Kerja Puskesmas Sragi II Kabupaten Pekalongan: Preeclampsia and Spousal Support: A Correlational Study in the Working Area of Sragi II Public Health Center, Pekalongan Regency - Ratnawati, Ratnawati; Dewi, Rika Amalia; Aryati, Dyah Putri; Kartikasari, Dian (Politeknik Kesehatan TNI AU Ciumbuleuit Bandung, 2025)
Introduction:Preeclampsia remains a significant maternal health challenge, more commonly found in developing countries than in developed ones. In Indonesia, the prevalence of preeclampsia is reported to be 3.3%. This condition is a serious pregnancy complication characterized by elevated blood pressure and the presence of protein in the urine. This study aims to assess the relationship between Spousal support and the incidence of preeclampsia among pregnant women in the working area of Sragi II Public Health Center, Pekalongan Regency. Methods:This research employed a descriptive design with a cross-sectional approach. Data collection used a total sampling technique, involving 66 pregnant women in their second and third trimesters. The research instruments included a questionnaire to assess husband support, as well as blood pressure measurements and urine protein tests. Data were analyzed using the Fisher Exact Test. Results:The findings revealed that 51.5% (34 respondents) received good support from their husbands. The majority of participants (98.5% or 65 individuals) did not experience preeclampsia. Based on statistical analysis using the Fisher Exact Test, a significance value of 1.000 was obtained, indicating no association between husband support and the incidence of preeclampsia among pregnant women in the Sragi II Health Center area. Recommendation:This study recommends that nursing professionals implement interventions involving Spousal support in the care of pregnant women, especially those experiencing or at risk of preeclampsia during pregnancy.